REDESIGN OF WORK PLACE AND SYSTEM WITH ERGONOMIC INTERVENTION IMPROVES THE PERFORMANCE OF THE SKT (HAND ROLLED CIGARETTE) ROLLERS AT CIGARETTE INDUSTRY “X” IN KEDIRI EAST JAVA - Sajiyo, H; Manuaba, Adnyana; Adiputra, Nyoman; Sutjana, Putu (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
In this research ergonomic intervention of the 4 main factors influencingperformance was conducted. The four main factors are : (a) intervention of humancovering the change in position of the SKT rollers from the position of facing oneanother into that of facing the same direction, from the hunchbacked sitting positioninto the upright one; (b) intervention of work equipment covering the changes inform, dimension, table and chair size, and layouts of space and work facilities ; (c)intervention of work system covering the changes in work process arrangement, rightand left hand movement, time allocated for active break and in the removal oftobacco which used to be done by the knockers but now is done by the rollers; (d)intervention of work environment, that is, exhaust installation to regulate thecirculation and wind humidity in the SKT rollers’ room. Redesign of place and worksystem with ergonomic intervention contribute to : (a) the decrease in work loadfrom medium category into light category; (b) the decrease in work tiredness frombeing very tired category into being not tired; (c) the decrease in musculoskeletalcomplaint from high category (being disturbed) into light category (beingundisturbed); (d) the decrease in medical treatment cost by 56,97%; (e) the increasein work productivity by 41,47%; (f) the increase in the SKT rollers’ salaries by15,10%; and (g) the increase in the company’s profit by 12,76%. Generally, redesignof place and work system can increase the performance of the SKT rollers at cigaretteindustry “X” at Kediri, East Java. Therefore, it has been suggested that the companycontinue to redesign the place and work system with ergonomic intervention in theother units.
Keywords: ergonomic, intervention, performance, work load, tiredness, musculoskeletal, productivity, income and profit